UNDERSTANDING A SUCCESSFUL ENTREPRENEUR—WHAT EXPERTS SAY: A PHENOMENOLOGICAL APPROACH STUDY - Gunawan Widjaja (ADISAM Publisher, 2023)
Having a deep understanding of entrepreneurial success is essential for anyone who wants to run a profitable business in an increasingly changing world. This study discusses the knowledge of successful entrepreneurs from the point of view of the experts we examine in the study of phenomenological approaches. We have conducted an electronic search for data on several literature sources, both books, scientific applications in the form of articles and websites and magazines that discuss issues of successful entrepreneurs viewed from various fire points of view. Meanwhile, the study that we run is under a phenomenological approach, namely the process of getting something phenomenal from several collected data. These processes include data coding, in-depth interpretation, and concluding by reasoning that the findings are close and relevant. In other words, the data findings are valid and convincing. Based on the explanation and discussion, we can say that understanding a successful entrepreneur is essential for individuals who want to run a business. That understanding must be supported by experts in entrepreneurship and related issues. Thus the presentation of this data to be useful for similar studies in the future.